تصوير مشاهد القيامة في القرآن الكريم )سورة الواقعة أنموذجا - صوالح, أحمد (جامعة الوادي university of eloued, 2018)
كان موضوع الدراسة "تصوير مشاهد القيامة في القرآن )سورة الواقعة أنموذجا(" يبرز لنا ما احتواه يوم القيامة من أحداث متسلسلة ومتتالية، ومن خلال الدراسة نلاحظ احتواء القرآن الكريم على مجموعة من صور هذا اليوم،وحديثه عنها بأسلوب فريد. كما عنت هذه الدراسة بتناول سورة الواقعة كأنموذجا،والتي تميزت بوسائلها البيانية،القريبة والبعيدة في تصوير مشاهد يوم القيامة،لحتوائها على حظ معتبر من صور هذا اليوم the subject of the study, "The Scenes of the Resurrection in the Qur'an" (Surat Al Waqiah) shows us what does the Day of Judgment contain of successive events, and through the study we observe that the Holy Qur'an contains a collection of images of this day. This study is also going to deal with this "Sura" as a model, which was characterized by its metaphoric sentences , in the description of the scenes of the Day of Judgment, because it contains a great amount of images about this day.
لغة